Robotic frameless brain biopsy system enhanced by facial mesh registration - Aydogmus, Omur; Talu, Muhammed Fatih (Wiley, 2025)
In this study, a new approach is presented that eliminates stereotactic frameworks and the use of markers, offering an alternative to traditional brain biopsy systems. The classical biopsy operation involves the registration of magnetic resonance (MR) and computed tomography (CT) information taken from the patient at different times. Typically, the surgeon's planning information, which takes an average of 4 h on MR, is transferred to CT, and the surgical operation commences. However, this approach necessitates two separate acquisitions (MR and CT), adversely affecting patient comfort and increasing the workload. In the proposed system, it is recommended to register MR-Depth camera data instead of MR-CT registration. To achieve this, a 3D face pattern is obtained from the data received from the depth camera attached to the robot arm and overlapped with the mesh obtained by segmentation of the MR. It was observed that registration with sub-millimeter precision was achieved using the CMFreg surface registration technique.
Keywords: 3D mesh generation; brain biopsy; image registration; image segmentation; medical image processing; medical robotics